Maternal Epstein-Barr Virus-Specific Antibodies and Risk of Infection in Ugandan Infants. (23rd October 2020) - Minab, Rana; Bu, Wei; Nguyen, Hanh; Wall, Abigail; Sholukh, Anton M; Huang, Meei-Li; Ortego, Michael; Krantz, Elizabeth M; Irvine, Michael; Casper, Corey; Orem, Jackson; McGuire, Andrew T; et al.
Abstract: Background: Epstein-Barr virus (EBV) infection is a major cause of malignancy worldwide. Maternal antibody is thought to prevent EBV infection because it is uncommon in early infancy. Maternal HIV infection is associated with an increased incidence of EBV infection in exposed infants, which we hypothesized results from impaired transfer of EBV-neutralizing maternal antibodies. Methods: Among Ugandan infants followed for EBV acquisition from birth, we measured antibody binding to EBV glycoproteins (gp350, gH/gL) involved in B-cell and epithelial-cell entry, as well as viral neutralization and antibody-dependent cellular cytotoxicity (ADCC) activity in plasma samples prior to infection. These serologic data were analyzed for differences between HIV-exposed uninfected (HEU) and HIV-unexposed (HUU) infants, and for associations with incident infant EBV infection. Results: HEU infants had significantly higher titers than HUU infants for all EBV-binding and neutralizing antibodies measured ( P < .01) but not ADCC activity, which was similar between groups. No antibody measure was associated with a decreased risk of EBV acquisition in the cohort. Conclusions: Our findings indicate that in this cohort maternal antibody did not protect infants against EBV infection through viral neutralization. The identification of protective nonneutralizing antibody functions would be invaluable for the development of an EBV vaccine.